Designed Patterning of Mesoporous Metal Films Based on Electrochemical Micelle Assembly Combined with Lithographical Techniques. Issue 12 (11th October 2019) - Lim, Hyunsoo; Kim, Jeonghun; Kani, Kenya; Masud, Mostafa Kamal; Park, Hyeongyu; Kim, Minjun; Alsheri, Saad M.; Ahamad, Tansir; Alhokbany, Norah; Na, Jongbeom; Malgras, Victor; Bando, Yoshio; et al.
Abstract: Mesoporous noble metals and their patterning techniques for obtaining unique patterned structures are highly attractive for electrocatalysis, photocatalysis, and optoelectronics device applications owing to their expedient properties such as high level of exposed active locations, cascade electrocatalytic sites, and large surface area. However, patterning techniques for mesoporous substrates are still limited to metal oxide and silica films, although there is growing demand for developing techniques related to patterning mesoporous metals. In this study, the first demonstration of mesoporous metal films on patterned gold (Au) substrates, prefabricated using photolithographic techniques, is reported. First, different growth rates of mesoporous Au metal films on patterned Au substrates are demonstrated by varying deposition times and voltages. In addition, mesoporous Au films are also fabricated on various patterns of Au substrates including stripe and mesh lines. An alternative fabrication method using a photoresist insulating mask also yields growth of mesoporous Au within the patterning. Moreover, patterned mesoporous films of palladium (Pd) and palladium–copper alloy (PdCu) are demonstrated on the same types of substrates to show versatility of this method. Patterned mesoporous Au films (PMGFs) show higher electrochemically active surface area (ECSA) and higher sensitivity toward glucose oxidation than nonpatterned mesoporous Au films (NMGF). Abstract : Patterned mesoporous metal films can be fabricated with photolithographic techniques. Not only can they be produced on various patterned substrates, but palladium and palladium–copper alloy pattern mesoporous films can also be fabricated. These patterned mesoporous metal films show high electrochemically‐active surface area and high sensitivity toward glucose oxidation applications.